Is There Association between ABO Blood Group and Congenital Heart Diseases in Neonates Born to Diabetic Mothers? - Abedelmonium M . Elmakki, Jowayria E. Tayrab, Mohammed Abbas, Eltayeb Tayrab, Dhafer Alqahtani, (Journal of Medical Biomedical and Applied Sciences, 2017)
PDF